2013
DOI: 10.1002/2013gl058479
|View full text |Cite
|
Sign up to set email alerts
|

Gypsum crystals observed in experimental and natural sea ice

Abstract: [1] Although gypsum has been predicted to precipitate in sea ice, it has never been observed. Here we provide the first report on gypsum precipitation in both experimental and natural sea ice. Crystals were identified by X-ray diffraction analysis. Based on their apparent distinguishing characteristics, the gypsum crystals were identified as being authigenic. The FREeZing CHEMistry (FREZCHEM) model results support our observations of both gypsum and ikaite precipitation at typical in situ sea ice temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 33 publications
6
64
0
Order By: Relevance
“…Sea ice is melted in the pool by circulating heated ethylene glycol through a closed-loop hose located at the bottom of the pool, allowing successive ice growth/melt experiments to be carried out during one winter. The experimental sea ice and brine exhibit similar physical and chemical properties to those observed in natural Arctic sea ice (Geilfus et al, 2013b;Hare et al, 2013). The experiment described herein was initiated from open water conditions on 11 January 2013 when the heater was turned off.…”
Section: Site Description Sampling and Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…Sea ice is melted in the pool by circulating heated ethylene glycol through a closed-loop hose located at the bottom of the pool, allowing successive ice growth/melt experiments to be carried out during one winter. The experimental sea ice and brine exhibit similar physical and chemical properties to those observed in natural Arctic sea ice (Geilfus et al, 2013b;Hare et al, 2013). The experiment described herein was initiated from open water conditions on 11 January 2013 when the heater was turned off.…”
Section: Site Description Sampling and Analysismentioning
confidence: 88%
“…As a result, the concentration of dissolved salts, including inorganic carbon, increases within the brine and promotes the precipitation of calcium carbonate crystals such as ikaite (CaCO 3 q 6H 2 O) (Marion, 2001). These crystals have been reported in both natural (Dieckmann et al, 2008;Nomura et al, 2013;Søgaard et al, 2013) and experimental sea ice (Geilfus et al, 2013b;Rysgaard et al, 2014) and have been suggested to be a key component of the carbonate system Fransson et al, 2013;.…”
mentioning
confidence: 82%
“…Actually, CaSO 4 is well known as a major mineral constituent (gypsum). Moreover, Marion and Farren (1999) and Geilfus et al (2013) pointed out CaSO 4 (gypsum) formation by seasalt fractionation on sea ice in polar regions. However, the origins of CaSO 4 particles in the Antarctic atmosphere remain unclear.…”
Section: Aerosol Constituents and Mixing States During The Jase Traversementioning
confidence: 99%
“…Hence, sea ice acts as a carbon pump during spring and summer. In contrast, during ice formation there are indications that sea ice acts as a CO 2 source as a consequence of the concentration of solutes in brines, CaCO 3 precipitation and microbial respiration (Geilfus et al, 2013b;Nomura et al, 2006;Tison et al, 2008).…”
Section: Introductionmentioning
confidence: 99%